RISK FACTORS OF ACUTE MYOCARDIAL INFARCTION AND THE NURSE’S PERFORMANCE - da Silva Fonseca Lima, Gabriely; Aparecida Borges, Mariana; Maturi Fernandes da Silva, Vitor; Zapparoli Trandafilov, Amanda (Health and Society, 2023)
Introduction: The highest morbimortality of acute myocardium infarction is directly related to the lifestyle adopted by the population. Therefore, the main modifiable risk factors for the development of pathologies are: arterial hypertension, diabetes mellitus, Hypercholesterolemia, smoking, obesity, and sedentary lifestyle. Furthermore, they can be effectively controlled through the prevention and monitoring from CNCDs in primary care, by means of HIPERDIA program’s and nursing appointment. Objective: To analyze, through a literature review, the role of nurses in the prevention and monitoring of CNCDs within primary health care. Methodology: This is an integrative review study, which used publications indexed in the electronic database of the regional portal of the VHL (Virtual Health Library), between 2016 and 2021. Results: 18 articles were used, corresponding to the factors of AMI risk, health education, nursing consultation and HIPERDIA. Conclusion: The high incidence and lethality of AMI, resulting from risk factors such as SAH and DM, in addition to lifestyle habits, was evidently portrayed by the selected articles. Furthermore, nurses who work in primary care need to intervene in the highlighted factors and exercise their role as a health educator, highlighting the importance of adopting a healthy lifestyle, in order to prevent patients from developing health issues, being referred to other levels of care and, consequently, generating more costs for the Unified Health System (SUS).